2017
DOI: 10.1161/circheartfailure.117.003862
|View full text |Cite
|
Sign up to set email alerts
|

INDIE-HFpEF (Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure With Preserved Ejection Fraction)

Abstract: Approximately half of patients with heart failure (HF) have preserved ejection fraction (HFpEF). There is no proven treatment that improves outcome. The pathophysiology of HFpEF is complex and includes left ventricular (LV) systolic and diastolic dysfunction, pulmonary vascular disease, endothelial dysfunction, and peripheral abnormalities. Multiple lines of evidence point to impaired nitric oxide-cyclic guanosine monophosphate (NO-cGMP) bioavailability as playing a central role in each of these abnormalities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 67 publications
1
40
1
Order By: Relevance
“…However, if cardiac hypertrophy and function are not different in response to isoproterenol or pressure overload in PKG KO mice compared with wild-type controls, 31 it is unlikely that targeting the cGMP-PKG pathway by administering soluble guanylate cyclase activators, natriuretic peptides, nitrates, and/or nitrite will either improve cardiac hypertrophy or have clinical benefit. This hypothesis and these data are consistent with the results of the Nitrate's Effect on Activity Tolerance in Heart Failure with Preserved Ejection Fraction (NEAT-HFpEF) trial 35 and would predict that the Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure With Preserved Ejection Fraction trial 57 would also not have a significant clinical benefit. FUTURE STUDIES/NOVEL APPROACHES TO TREATMENT Future studies are needed to develop treatments to improve symptoms and survival in patients with HFpEF.…”
Section: Predictions/trialssupporting
confidence: 70%
See 1 more Smart Citation
“…However, if cardiac hypertrophy and function are not different in response to isoproterenol or pressure overload in PKG KO mice compared with wild-type controls, 31 it is unlikely that targeting the cGMP-PKG pathway by administering soluble guanylate cyclase activators, natriuretic peptides, nitrates, and/or nitrite will either improve cardiac hypertrophy or have clinical benefit. This hypothesis and these data are consistent with the results of the Nitrate's Effect on Activity Tolerance in Heart Failure with Preserved Ejection Fraction (NEAT-HFpEF) trial 35 and would predict that the Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure With Preserved Ejection Fraction trial 57 would also not have a significant clinical benefit. FUTURE STUDIES/NOVEL APPROACHES TO TREATMENT Future studies are needed to develop treatments to improve symptoms and survival in patients with HFpEF.…”
Section: Predictions/trialssupporting
confidence: 70%
“…However, treatment with isosorbide mononitrate did not have clinical benefit. 35 The Inorganic Nitrite Delivery to Improve Exercise Capacity in Heart Failure With Preserved Ejection Fraction trial 57 focuses on impaired NO-cGMP signaling as a central pathway leading to HFpEF, with an alternative approach to restore NO-cGMP signaling via the addition of an inorganic nitrite. However, if cardiac hypertrophy and function are not different in response to isoproterenol or pressure overload in PKG KO mice compared with wild-type controls, 31 it is unlikely that targeting the cGMP-PKG pathway by administering soluble guanylate cyclase activators, natriuretic peptides, nitrates, and/or nitrite will either improve cardiac hypertrophy or have clinical benefit.…”
Section: Predictions/trialsmentioning
confidence: 99%
“…26,27 In HFpEF, the recent greater molecular understanding of endothelial damage and oxidative stress due to the proinflammatory state would imply the concept of a pulmonary microvessel vasculopathy susceptible to benefits by interventions targeting the impaired nitric oxide-cGMP bioavailability pathway by improving the regional lung perfusion and, for instance, the VD/VT pattern during exercise. 28,29 In conclusion, evidence provided by Van Iterson et al 15 refreshes some knowledge on the ventilatory mediators of exercise intolerance and remarkably enriches the picture, especially prospecting for new insights on patients with HFpEF. Findings support the hypothesis that HFpEF and HFrEF may be two distinct entities also in terms of ventilatory response to physical challenge.…”
Section: This Article Refers To 'Physiological Dead Space and Arteriamentioning
confidence: 86%
“…This way of breathing is typical of some relaxing activities such as rosarium, yoga, and listening to music that might overall benefit VE efficiency, at least in HFrEF . In HFpEF, the recent greater molecular understanding of endothelial damage and oxidative stress due to the proinflammatory state would imply the concept of a pulmonary microvessel vasculopathy susceptible to benefits by interventions targeting the impaired nitric oxide–cGMP bioavailability pathway by improving the regional lung perfusion and, for instance, the VD/VT pattern during exercise …”
mentioning
confidence: 97%
“…Other investigators have recently reported that inhaled and intravenous nitrite also reduces PAOP during exercise in patients with Group 2 PH (particularly the subset of patients with heart failure with preserved ejection fraction), which is associated with improved exercise capacity (13,14). This drug is now being evaluated by the National Heart, Lung, and Blood Institute Heart Failure L772 EMERGING THERAPEUTICS IN PH Network and is under development by United Therapeutics (NCT02742129) (109).…”
Section: Inhaled Nitritementioning
confidence: 99%